2021
DOI: 10.1175/bams-d-20-0088.1
|View full text |Cite
|
Sign up to set email alerts
|

The Advanced Very High Resolution Radiometer: Contributing to Earth Observations for over 40 Years

Abstract: Capsule The last Advanced Very High Resolution Radiometer (AVHRR) was successfully launched and put into operations in 2018. AVHRRs have been observing the Earth continuously for over forty years and their data provide an invaluable record for oceanographic, terrestrial, meteorological and climate studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 83 publications
0
7
0
Order By: Relevance
“…High resolution images of polar orbiting measurement are obtained from the Advanced Very High Resolution Radiometer (AVHRR; Kalluri et al., 2021) onboard the Meteorological Operational (MetOp) satellite program from the European Organisation for the Exploitation of Meteorological Satellites (EUMETSAT). AVHRR scans the whole Earth twice a day with 6 spectral bands having a 1.1 km spatial resolution.…”
Section: Methodsmentioning
confidence: 99%
“…High resolution images of polar orbiting measurement are obtained from the Advanced Very High Resolution Radiometer (AVHRR; Kalluri et al., 2021) onboard the Meteorological Operational (MetOp) satellite program from the European Organisation for the Exploitation of Meteorological Satellites (EUMETSAT). AVHRR scans the whole Earth twice a day with 6 spectral bands having a 1.1 km spatial resolution.…”
Section: Methodsmentioning
confidence: 99%
“…METOP-A flew in a descending orbit with an equatorial overpass at 07:50, while METOP’s-B and -C fly in a ~09:30 descending orbit. METOP-C, launched in 2018 carrying the last AVHRR instrument, which with NOAA, has maintained a continuous 40+ year global data record of land surface conditions, the longest satellite-based record of global monitoring [ 68 ].…”
Section: High-impact Pioneering Satellites From the 1970s To The Earl...mentioning
confidence: 99%
“…Currently, global SSH observations are primarily achieved by spaceborne radar altimeters, which retrieve the two-dimensional SSH field (∼25 km) from altimetry observations [1,2]. In addition to satellite altimetry observations, satellites also routinely observe other ocean dynamic parameters, including SST, which can be observed at relatively higher resolution [3]. A large number of studies have revealed that SSH and SST have a close dynamic relationship [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%